Prof. Dr. Lukács János, Editor-in-Chief - Lukács, János (Public Finance Quarterly, 2023)
I have often wondered whether we should have a Foreword in our journal, because as the saying goes, good wine does not need a label. Finally, as you can see, I thought that it might not be superfluous to preface this issue with an enthusiastic introduction, summarising the essence of the many articles in it, sharing my feelings and experiences of reading them, and presenting the general lessons of the research results written with professional thoroughness